Variations of Mandarin Slang on Weibo: A Linguistic Trend in Social Media - Kezia Tabitha Purnomo; Muhammad Farhan Masrur; Catari Alam (Universitas Negeri Surabaya, 2025)
Communication plays a vital role in human social interaction, with language serving as the primary tool for conveying messages, expressing identity, and shaping cultural development. Mandarin, as one of the most widely spoken languages, includes both formal and informal variations, such as slang. Slang is an evolving linguistic phenomenon that reflects social and cultural dynamics, particularly among young people. This study explores the characteristics, formation mechanisms, and social functions of Mandarin slang, with a focus on its usage on Weibo, one of China's most influential social media platforms. The research adopts a qualitative descriptive approach to analyze slang terms used in digital interactions between September and December 2023. The findings indicate that slang in Mandarin follows various linguistic patterns, including phonetic changes, abbreviations, metaphors, loanwords, and morphological adaptations. Additionally, slang serves multiple functions, such as strengthening social identity, fostering group cohesion, and enabling creative self-expression. Weibo significantly contributes to the dissemination and evolution of slang, as public figures, celebrities, and media organizations actively engage in language innovation through their posts. This study provides insights into the dynamic role of digital platforms in shaping modern language trends and highlights the impact of slang on communication patterns among Chinese youth.